An Investigation of the Antecedents to Marketing Mix Strategy Implementation - Manggala Putri, Syah Amelia; Hayati, Safaah Restuning; Firmansyah, Eka Jati Rahayu (Ihtifaz: Journal of Islamic Economics, Finance, and Banking, 2020)
Introduction to The Problem: Been established for 282 years (2019), Pondok Pesantren Sidogiri was one of the oldest Islamic educational institutions in Indonesia. With its approximately 11,000 students, the institution was potentially economic to develop. The development effort was started in 1961 by establishing Koperasi Pondok Pesantren which focused on how to fulfill its students’ needs. Kopontren Sidogiri was currently the main actor in a minimarket business competition in East Java. With its trading activities earning IDR 1 trillion per year, Kopontren Sidogiri could give a welfare impact to the community and Pondok Pesantren Sidogiri.Purpose/Objective Study: The research aims to examine Kopontren Sidogiri’s operational description and marketing-mix implementation in retail business in the 4.0 era.Design/Methodology/Approach: The research was conducted using a qualitative method. According to the theme of the discussion, this research was field research. The research was a descriptive case study performed at Koperasi Pondok Pesantren Sidogiri. Sampling was conducted using a purposive sampling technique. The research sample consisted of a steering committee, managers, staff, and experts. The secondary data were collected from several findings relevant to this study. Data validity was tested using a triangulation technique.Findings: Strategies implemented included marketing mix (4Ps) i.e. product, place, price, and promotion. The achievement gave an inclusive and modern image to Koperasi Pesantren. Meanwhile, place strengthening was by building Toko Basmalah in the areas where alumni of Pondok Pesantren Sidogiri lived, creating loyal market targets. Moreover, price strengthening was by using a retail price in a product sale, encouraging the sale, and making effective profits. The promotion was by branding Pondok Pesantren Sidogiri, creating customers’ trust, and spreading positive information about Minimarket Basmallah to people (word of mouth).